Venous thromboembolism during three muslim pilgrimage seasons - Abdulsalam A. Noorwali (Egyptian Journal of Chest Disease and Tuberculosis)
Background Acute pulmonary embolism (PE) is a potentially fatal condition for which prompt recognition, risk assessment and appropriate treatment must be implemented to reduce mortality and morbidity. This study was planned to analyze all cases of venous thromboembolism (VTE) admitted to the tertiary care hospital during three successive Muslim hajj seasons.